Exploration of developmental toxicity mechanism of emerging environmental contaminants - Tao CHEN; Yunhui ZHANG (环境与职业医学)
The health risk posed by emerging environmental contaminants has become a public concern. Increasing evidence indicate that maternal exposure to multiple emerging environmental contaminants disrupts embryonic development. However, the underlying mechanisms of this developmental toxicity remain unclear, hindering risk assessment and prevention efforts. In this column, the developmental toxicity mechanisms of various emerging pollutants were studied by employing model animals, big data analysis, and single-cell sequencing. We hope that this column will encourage further research into the developmental toxicity mechanisms of emerging environmental contaminants and provide a scientific base for policy-making.